2020
DOI: 10.1016/j.ijfatigue.2020.105573
|View full text |Cite
|
Sign up to set email alerts
|

Competing mechanisms of particle fracture, decohesion and slip-driven fatigue crack nucleation in a PM nickel superalloy

Abstract: Fatigue cracks may initiate around non-metallic inclusions via particle fracture, particle decohesion and slipdriven nucleation. Cohesive zone techniques within microstructurally faithful crystal plasticity modelling validated by micromechanical experiments (HR-DIC and HR-EBSD) are employed to investigate these nucleation phenomena. Particle fracture and decohesion lead to stress redistribution which influences subsequent energy storage driving slip-driven fatigue crack nucleation. Particle fracture and decohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Therefore, an in-depth understanding of the role of NMIs and their neighboring microstructure will provide critical insights on the causes of variation in fatigue life. Plasticity associated with inclusions embedded in metallic matrix (nickel or steel as a continuum medium) was investigated using finite element analyses (FEA) [18][19][20][21] and more recently FEA coupled with high resolution-digital image correlation (HR-DIC) techniques [22]. These studies demonstrated accumulation of plastic deformation at the "NMI/metallic matrix" interface under cyclic loading in the presence or not of initial damage at the NMI/matrix interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an in-depth understanding of the role of NMIs and their neighboring microstructure will provide critical insights on the causes of variation in fatigue life. Plasticity associated with inclusions embedded in metallic matrix (nickel or steel as a continuum medium) was investigated using finite element analyses (FEA) [18][19][20][21] and more recently FEA coupled with high resolution-digital image correlation (HR-DIC) techniques [22]. These studies demonstrated accumulation of plastic deformation at the "NMI/metallic matrix" interface under cyclic loading in the presence or not of initial damage at the NMI/matrix interface.…”
Section: Introductionmentioning
confidence: 99%
“…An uncoupled relationship between normal and shear traction is used since we expect the normal traction to be the primary driver of decohesion as demonstrated by Zhang et al 34 and Bergsmo and Dunne. 35 In these studies, decohesion between the metal-oxide interface and oxide particle fracture is observed experimentally and shown to correlate with high interfacial normal stresses and maximum principal stress normal to the fractured plane, respectively. Also, the significant stress redistribution that occurs once the oxide agglomeratematrix interface decoheres is shown to significantly change the energy distribution local to the oxide particle.…”
Section: Hard Inclusion and Cohesive Zone Modellingmentioning
confidence: 99%
“…Material data for the metal-oxide interface was obtained from Bergsmo and Dunne. 35 This work argued that the process of decohesion is stress controlled and that failure occurs in a brittle manner releasing all its traction after reaching a peak value. Thus, the choice of a linear traction-separation relation is justified as the shape of the curve would be of secondary importance only.…”
Section: Hard Inclusion and Cohesive Zone Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue decohesion occurs when the maximum normal stress around a concentrator is equal to the metal cohesive strength. This area was studied by Gołaski, Zakrzewski, Lardner, Bergsmo [ 22 ] and others.…”
Section: Introductionmentioning
confidence: 99%